Penggunaan Aplikasi Kahoot dalam Meningkatkan Kreatifitas Mahasiswa - Melawati, Reni (Jurnal Penelitian, 2022)
The  main purpose of this research is to find out the benefits of media kahoot learning in increasing student creativity. This matter because the world has entered the 4.0 era by having various types of thecnological advances. Then the method used in this research is a literature review ad documentation data. This stdy is not only a concept theory but also criticizes the study of existing theories to stregthen the study this literature. Kahoot is concidered a good media to use in supporting activities learning at the school or college level. Kahoot can increase the creativity of each student by providing opportunities to process their own use both in term of questions, answers of methods provided by kahoot it self. It is hoped that kahoot will always develop for can become an online platform that can providr full benefits to everyone users, sepecially for students who are prepared to becpme educators who must be ready for new things. Kahoot that is rated can improv student creativity has spread throughout the world including Indonesia.